The GC-MS fingerprints of Nicotiana tabacum L. extract and propensity for renal impairment and modulation of serum triglycerides in Wistar rats. - Faoziyat A. Sulaiman; Mikail O. Nafiu; Babalola O. Yusuf; Hamdalat F. Muritala; Sherif B. Adeyemi; Sikemi A. Omar; Kehinde A. Dosumu; Zainab J. Adeoti; Oluwafunmilayo A. Adegbesan; Basirat O. Busari; David A. Otohinoyi; Damilare Rotimi; et al. (GarVal Editorial Ltda., 2020)
Context: Nicotiana tabacum is an herbaceous plant mostly known as tobacco. Locally, people do extract this plant with cow urine, they call it "Adimenu" and they claimed it is effective in managing various ailments, even with taking just a spoonful of the extract. Thus, profiling the toxicity and or otherwise of the cow-urine extracted tobacco plant cannot be overemphasized. Aims: To characterize the cow urine extracts of N. tabacum and evaluated the sub-acute toxicity of smokeless exposure in male Wistar rats. Methods: Forty male Wistar rats were randomly assigned into groups and exposed to different doses (50, 100 and 200 mg/kg body weight) of N. tabacum extract for 7 and 28 days, after which the animals were sacrificed for the biochemical assays. Results: The GC-MS analysis revealed 21 compounds in the N. tabacum extract. As expected, nicotine was predominant among the identified compounds. The sub-acute exposure of rats to cow-urine extract of N. tabacum extract might have altered rat metabolic homeostasis, triggering adaptive mechanisms, while impairing renal functions. The N. tabacum extract also modulated (p<0.05) rat serum lipid profile when compared with control. Conclusions: Findings in this study suggest that the cow-urine extract of N. tabacum exposure in male Wistar rats might have perturbed rat renal functions as well as modulated serum lipid profile. This research, therefore, recommends to local consumers to be cautious of the rate at which they consume their regular "Adimenu".